Effect of Coconut Water and Benzyl Adenine with Different Concentrations on Potato Tissue Culture (Solanum tuberosum L.) Var. Granola - Hana S. Tomatala; Simon Raharjo; Meitty L. Hehanussa (Faculty of Agriculture, Pattimura University, 2023)
This study aimed to determine the effect of giving coconut water and the right concentration of benzyl adenine in MS media for potato tissue culture of Granola variety. The study was carried out from November to January 2022, in the Plant Tissue Culture Laboratory of the Faculty of Agriculture, Pattimura University, Ambon. This study used a 2-factor completely randomized design (CRD); the first factor was the concentration of coconut water 0 with 100 ml/l, and the second factor was the concentration of BA consisting of 0.1,2,3,4 mg/l. The study was conducted with 7 replicates and each replication consisted of 5 explants in each culture bottle, so that there were 350 cultures as the unit of observation. The variables observed in this study included the number of shoots, the number of internodes, the number of branches, and the number of roots per plantlet. The results showed that the concentration of coconut water 0 and 100 ml/l had an effect on the number of internodes and the number of roots at 4 weeks after planting. Benzyl adenine at 0, 1, 2, 3 and 4 mg/l had an effect on the variable number of shoots at 8 WAP and the number of internodes at 2 - 8 WAP; which also applies to the number of roots. Whereas, the interaction between both factors affected the number of internodes at 4, 6, and 8 weeks, which also applies to the number of roots.